Gendered experiences of fragility and displacement in climate crises: Insights from Chimanimani, Chipinge and Tsholotsho, Zimbabwe - Ncube, Cornelius; Synnestvedt, Thea; Takaindisa, Joyce; Maphosa, Mandlenkosi; Maviza, Gracsious; Sithole, Mkhokheli; Tarusarira, Joram; Ndlovu, Sindiso; Gumindoga, Webster; Campbell, Raramai; Mateveke, Pauline; Gadu, Siyaxola; et al. (2025)
The overarching objective of this research was to explore the climate, displacement, peace, and security nexus through a gendered lens in the Chimanimani, Chipinge, and Tsholotsho districts in Zimbabwe. Communities in these regions have faced severe climate change impacts, with unique challenges for women and men. In Chimanimani and Tsholotsho, cyclones have caused devastating floods that displaced families and disrupted local livelihoods. Meanwhile, Chipinge has a notable population of refugees, adding to pressures on food, land, and water systems. Based on data generated through participatory methods, this report focuses on how climate-induced fragility and displacement affect men and women differently and the unique challenges different genders face in climate crises. The aim is to guide policymakers in recognising and addressing gender within the broader discourse of climate change, fragility, and displacement